Inhibition of IL-34 Unveils Tissue-Selectivity and Is Sufficient to Reduce Microglial Proliferation in a Model of Chronic Neurodegeneration - Obst, Juliane; Simon, Emilie; Martin-Estebane, Maria; Pipi, Elena; Barkwill, Liana M.; Gonzalez-Rivera, Ivette; Buchanan, Fergus; Prescott, Alan R.; Faust, Dorte; Fox, Simon; Brownlees, Janet; Taylor, Debra; et al. (Frontiers in Immunology, 2020)
The proliferation and activation of microglia, the resident macrophages in the brain, is a hallmark of many neurodegenerative diseases such as Alzheimer's disease (AD) and prion disease. Colony stimulating factor 1 receptor (CSF1R) is critically involved in regulating microglial proliferation, and CSF1R blocking strategies have been recently used to modulate microglia in neurodegenerative diseases. However, CSF1R is broadly expressed by many cell types and the impact of its inhibition on the innate immune system is still unclear. CSF1R can be activated by two independent ligands, CSF-1 and interleukin 34 (IL-34). Recently, it has been reported that microglia development and maintenance depend on IL-34 signaling. In this study, we evaluate the inhibition of IL-34 as a novel strategy to reduce microglial proliferation in the ME7 model of prion disease. Selective inhibition of IL-34 showed no effects on peripheral macrophage populations in healthy mice, avoiding the side effects observed after CSF1R inhibition on the systemic compartment. However, we observed a reduction in microglial proliferation after IL-34 inhibition in prion-diseased mice, indicating that microglia could be more specifically targeted by reducing IL-34. Overall, our results highlight the challenges of targeting the CSF1R/IL34 axis in the systemic and central compartments, important for framing any therapeutic effort to tackle microglia/macrophage numbers during brain disease.